2021
DOI: 10.1007/s12262-021-02998-6
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Immersive Technology in Global Surgery Education

Abstract: The second wave of immersive reality technology is required that enhances and exploits current applications, empirical evidence and worldwide interest. If this is successful, low-and middle-income countries will have improved access, less costs and reduced practical limitations. Affordability, availability, accessibility and appropriateness are determinates, and help from several innovative areas can achieve these targets. Artificial intelligence will allow autonomous support of trainees to accelerate their sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Another study using google carboard VR headset, users were reported to specifically do better on questions regarding spatial awareness (Rasheed et al, 2015). Lastly since the start of the COVID-19 pandemic some studies have also looked into the possibility of teaching medical skills thanks to VR, with mixed results in terms of learning (Lohre et al, 2020;Birrenbach et al, 2021;Clarke, 2021;Pears and Konstantinidis, 2021). However, in none of these studies presence was measured.…”
Section: Presence and Learningmentioning
confidence: 99%
“…Another study using google carboard VR headset, users were reported to specifically do better on questions regarding spatial awareness (Rasheed et al, 2015). Lastly since the start of the COVID-19 pandemic some studies have also looked into the possibility of teaching medical skills thanks to VR, with mixed results in terms of learning (Lohre et al, 2020;Birrenbach et al, 2021;Clarke, 2021;Pears and Konstantinidis, 2021). However, in none of these studies presence was measured.…”
Section: Presence and Learningmentioning
confidence: 99%
“…e disadvantage is that it is vulnerable to network attacks. Nodes with high rights and interests are easier to keep accounts and lose impartiality [18].…”
Section: Consensus Mechanismmentioning
confidence: 99%
“…In education, we acknowledge it is time to revisit traditional teaching pedagogies and make thoughtful shifts in teaching-learning in response to the impending changes in higher education (Pears & Konstantinidis, 2021). The American Association of Colleges of Nursing's vision for academic nursing has incorporated the use of informatics and technology within the Essentials to support healthcare processes and clinical thinking to positively impact patient outcomes.…”
Section: Nur S Ing Educ Ationmentioning
confidence: 99%